1984
DOI: 10.1139/v84-003
|View full text |Cite
|
Sign up to set email alerts
|

Permanganate peroxidation of cyclohexene.I. The unusual effect of turbulent stirring and dilution upon glycol yields

Abstract: (1984).Yields of cis-l,2-cyclohexanediol formed by the reaction of methanol-water solutions of potassium permanganate with cyclohexene varied from nearly zero to a high of 84% as a function of stirring efficiency and dilution. This unusual effect is attributed to the formation of an intermediate hypomanganate ester ion which after formation may undergo reaction [ I ] with water to form the glycol or [2] with excess Mn04-to form higher oxidation products. The factor of increased stirring and dilution reduced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…[1][2][3] The yields of diols, however, are seldom above 50% though they can be improved with phase transfer catalysis [4][5][6] or by increased stirring. 7 The preparation and absorption spectrum of a stable solution of manganese (V) diesters by reacting alkenes with pulverised potassium permanganate in dichloromethane and benzyltriethylammonium chloride as a phase transfer agent has been reported 8,9 by Ogino and his group. It is probable that the intermediate manganate (V) diester is more stable under these conditions because it would be complexed with the quaternary ammonium ion and the hydrolysis reaction would be suppressed by the absence of water.…”
mentioning
confidence: 99%
“…[1][2][3] The yields of diols, however, are seldom above 50% though they can be improved with phase transfer catalysis [4][5][6] or by increased stirring. 7 The preparation and absorption spectrum of a stable solution of manganese (V) diesters by reacting alkenes with pulverised potassium permanganate in dichloromethane and benzyltriethylammonium chloride as a phase transfer agent has been reported 8,9 by Ogino and his group. It is probable that the intermediate manganate (V) diester is more stable under these conditions because it would be complexed with the quaternary ammonium ion and the hydrolysis reaction would be suppressed by the absence of water.…”
mentioning
confidence: 99%
“…(3) As the reaction proceeds and MnO 2 is formed, increased viscosity, clumping of the precipitate, and entrainment of the alkene result. More efficient stirring can, at least in part, offset these effects and can greatly increase glycol yields as was previously shown for cyclohexene. , …”
Section: Data and Discussionmentioning
confidence: 68%
“…The preparation of cis -1,2-cyclohexanediol by permanganate oxidation of cyclohexene has been studied extensively, and it was demonstrated that excellent yields <87% can be obtained by a turbulent stirring technique. A mechanism was also developed …”
Section: Introductionmentioning
confidence: 99%
“…Known unsaturated lactam 8 , which can be prepared in a multigram scale,21 was chosen as the starting material for a cis hydroxylation to give racemic 4,5‐dihydroxylactam 9 . Among the various options for such a reaction, the addition of an aqueous solution of KMnO 4 to a vigorously stirred alkaline solution of the substrate in water at 0 °C worked best in terms of product recovery and yield after work‐up 22,23. Reagent concentrations, pH, and addition rate were critical to avoid either overoxidation or migration of the double bond to give the corresponding α,β‐unsaturated lactam.…”
Section: Resultsmentioning
confidence: 99%